2022
DOI: 10.2174/1389450122666211008140811
|View full text |Cite
|
Sign up to set email alerts
|

miRNAs as Modulators of Cholesterol in Breast Cancer Stem Cells: An Approach to Overcome Drug Resistance in Cancer

Abstract: : It has been postulated that a small number of cancer stem cells (CSCs) buried in tumour mass drive cancer growth and impart cancer drug resistance. However, their eradication has not been achieved so far as the mechanistic understanding around CSCs’ role in cancer development and growth is limited. The cholesterol accumulation and efflux processes have been shown to play an important role in maintaining cell’s integrity and its sensitivity towards drugs, as altered cholesterol pathways contribute to cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Intriguing new data suggest that miRNAs will be used to overcome resistance. Bernice Monchusi and Mandeep Kaur suggested that targeting the miRNAs hsa-miR-34a-5p and hsa-miR-373-3p could provide a way to alter the cell's response to drugs via modulating cholesterol pathways in cancer stem cells [99].…”
Section: Discussionmentioning
confidence: 99%
“…Intriguing new data suggest that miRNAs will be used to overcome resistance. Bernice Monchusi and Mandeep Kaur suggested that targeting the miRNAs hsa-miR-34a-5p and hsa-miR-373-3p could provide a way to alter the cell's response to drugs via modulating cholesterol pathways in cancer stem cells [99].…”
Section: Discussionmentioning
confidence: 99%
“…They are small (~18-25 nucleotides) nonencoding RNAs that can modulate the expression of the genes involved in the pathway [87]. A recent study using bioinformatics analysis [88] has revealed that hsa-miR-34a-5p and hsa-miR-373-3p can affect the expression of several genes related to CHOL, including INSIG2. This gene codes for insulin-induced gene 2, an endoplasmic reticulum protein that acts as a negative regulator of CHOL biosynthesis by retaining the SCAP-SREBP complex in the endoplasmic reticulum.…”
Section: Cholesterol Biosynthesis Mammary Stem Cells and Breast Cance...mentioning
confidence: 99%